IMPACT OF THE PRADHAN MANTRI MUDRA YOJANA (PMMY) ON RURAL ENTREPRENEURSHIP DEVELOPMENT - Sheba, M. Surath; Vasanthi, T. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Pradhan Mantri Mudra Yojana (PMMY) was introduced in 2015 to promote entrepreneurship and self-reliance among small-scale enterprises, particularly in rural India. This study evaluates the scheme’s impact on fostering rural entrepreneurship by analyzing credit accessibility, income generation, and employment creation. Using primary and secondary data from rural beneficiaries in Tamil Nadu, the paper highlights the effectiveness of PMMY in enhancing rural entrepreneurial activities. While the scheme has shown positive outcomes in terms of increased business ventures, challenges such as repayment defaults and lack of financial literacy remain.